Performance, methane production, and beef lipid profile of young bulls finished in feedlot - Barbara Martins Rodrigues; Ramon Costa Alvarenga; Dante Pazzanese Duarte Lanna; Alexandre Berndt; Fernando Antônio de Souza; Leandro Sâmia Lopes (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to evaluate the growth performance, enteric methane production, carcass traits, and fatty acid profile of the Longissimus thoracis muscle of young Nellore and Angus x Nellore beef bulls fed with a high-lipid diet and finished in feedlot. Fifty young bulls were evaluated, being divided into two groups: Nellore (n=25) and Angus × Nellore (n=25), randomly assigned to four pens in a completely randomized design. The feedlot phase covered 105 days of feed. The diet (80% concentrate) was formulated to meet or exceed beef cattle requirements to reach an average daily gain of 1.6 kg per day. The crossbred animals showed a higher dry matter intake, feed efficiency, initial body weight, final body weight, average daily gain, average daily carcass gain, hot carcass weight, and percentage of rib. However, dressing percentage was similar for both groups. The Nellore animals produced more enteric methane, expressed in g kg-1 average daily gain), but, also, higher concentrations of polyunsaturated fatty acids and conjugated linoleic acid. The two genetic groups show satisfactory growth rates, but the crossbred animals present a better growth performance and produce less methane per unit of beef. The animal’s genetic composition modifies its fatty acid profile.